Mosquito-borne haemorrhagic fevers of South and South-East Asia - Halstead, Scott B. (1966)
During the past decade outbreaks of a severe haemorrhagic disease caused by dengue viruses of multiple types have been reported in the Philippines, Thailand, Malaysia, Viet-Nam and eastern India. In many of these outbreaks chikungunya virus, a group A arbovirus, was simultaneously the cause of similar but probably milder disease. Both these viruses appear to be able to be able to produce classical dengue fever in some individuals and disease with haemorrhagic manifestations in others. Because of the growing public health importance and the progressive spread of this disease a unified review of its clinical and epidemiological features has been needed. This paper presents the history and salient clinical features of mosquito-borne haemorrhagic fever and summarizes recent epidemiological studies and current diagnostic and control methods.